The Effect of the Traditional Game of Congklak on the Cognitive Development of Children Aged 5–6 Years at RA Darussaadah Chaidir Adam - Rara Marnita; Riza Novitri; Rahmanita; Saparia Fitriani; Fatmi Fauzani (CV Edujavare Publishing, 2026)
Cognitive development is a crucial aspect of early childhood education as it forms the foundation for thinking, reasoning, and problem-solving skills in subsequent educational stages. One approach to stimulating children’s cognitive development is through play activities, particularly by utilising traditional games that are concrete in nature and suited to children’s characteristics. The traditional game of congklak is considered to have educational potential as it involves counting, logical thinking, concentration, and decision-making. This study aims to determine the effect of the traditional game of congklak on the cognitive development of 5–6-year-old children at RA Darussaadah Chaidir Adam. This study employed a quantitative approach using a quasi-experimental design with a pre-test–post-test model. The research subjects were children aged 5–6 years, all of whom were included as the study sample. Data collection was conducted through observation of the children’s cognitive development, whilst data analysis utilised the t-test or Wilcoxon test, depending on the data characteristics, alongside N-Gain calculations. The results of the study indicate that the traditional game of congklak has a significant effect on enhancing the cognitive development of children aged 5–6 years. Consequently, the game of congklak can serve as an effective alternative learning medium to stimulate children’s cognitive development in RA/PAUD institutions.